Perbandingan Pendapatan Usahatani Sayuran Dataran Tinggi Kentang Dan Bawang Daun Di Desa Sinsingon Barat Kecamatan Passi Timur Kabupaten Bolaang Mongondow - Pianaung, Novia Putri; Kaunang, Rine; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2024)
This study aims to calculate the income of potato and green onion upland vegetable farming in West Sinsingon Village, East Passi District, Bolaang Mongondow Regency in one growing season. This study uses data from the growing season from October 2022 to January 2023. The total samples are 10 potato farmer samples and 10 leek farmer samples. Data were analyzed using mathematical calculations using the formula: I = R-C (I = Income, R = Revenue, and C = Expenditures). The research results showed that the average potato farming production was 20.827.59 kg. The average selling price of potatoes is IDR 13.000/kg, resulting in an average income of IDR 191.775.135.72/hectare. The average leek farming income produces a production of 12.585.03 kg. The average selling price is IDR 9.000/kg, resulting in an average income of IDR 51.493.375.11/hectare. Potato farming and leek farming in West Sinsingon Village, East Passi District are profitable. The average income from potato farming is relatively higher than the average income from leek farming with a difference of IDR 140.281.760.61/hectare/planting season.